The magic finger - Dahl, Roald (Puffin, 2016)
Every Saturday morning the Greg family goes off to shoot animals and birds. But the girl who lives next door hates hunting. Now it's made her so angry she's Put the Magic Finger on Them All. And very strange things have begun to happen...